Oropharyngeal candidiasis - interdisciplinary aspects of childhood medicine - S.O. Mokia-Serbina; V.I. Fesenko (Zaslavsky O.Yu., 2024)
Scientific research in recent years has increased the interest of clinicians in the role of microorganisms in maintaining health and the occurrence of diseases. In most cases, fungal lesions of the oral mucosa are a manifestation of numerous somatic diseases and the results of their treatment and contribute to complications. To write this article, the information was searched using the databases Scopus, Web of Science, Med Zine, Pub Med, Google Scholar, the new version of the International Classification of Diseases (ICD-11) and the Standards of Care "Rational use of antibacterial and antifungal drugs for therapeutic and prophylactic purposes" (2023) were taken into account. The review presents data from the world literature on the role of fungal infection in the development of oropharyngeal candidiasis in children, current perspectives on the mechanism of its formation, clinical manifestations and diagnosis. A comparative characterization of the recommendations of national and foreign guidelines and a generalization of retrospective analyzes on the feasibility of prescribing systemic antifungal drugs for candidal lesions of the oral mucosa and possible methods of correction for mycoecological disorders in children are given. In the context of the presented problem, an integrated approach of a primary care physician, dentist and pediatrician to the diagnosis and treatment of oropharyngeal candidiasis in children is recommended. Timely diagnosis of oropharyngeal candidiasis in children, individual selection of antifungal drugs, synbiotics and multicomponent agents based on probiotics should be a priority area of joint work of general practitioners - family physicians, pediatricians and dentists.